2015
DOI: 10.1364/oe.24.00a123
|View full text |Cite
|
Sign up to set email alerts
|

Distance within colloidal dimers probed by rotation-induced oscillations of scattered light

Abstract: Abstract:Aggregation processes of colloidal particles are of broad scientific and technological relevance. The earliest stage of aggregation, when dimers appear in an ensemble of single particles, is very important to characterize because it opens routes for further aggregation processes. Furthermore, it represents the most sensitive phase of diagnostic aggregation assays. Here, we characterize dimers by rotating them in a magnetic field and by recording the angle dependence of light scattering. At small scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…38 With a detection angle of the scattered light at 90 degrees, Ranzoni et al 43 demonstrated that the concentration of PSA in undiluted blood plasma could be measured in the low picomolar range, by recording the amplitude of the 2f signal (at twice the driving frequency). Vliembergen et al 124,125 have extended the optical detection method by analyzing the rotation-angle dependent scattering signals. Sharp peaks in the spectrum allowed them to measure nanometer-scale inter-particle distances within the clusters.…”
Section: Biomarker Detection and Concentration Determinationmentioning
confidence: 99%
“…38 With a detection angle of the scattered light at 90 degrees, Ranzoni et al 43 demonstrated that the concentration of PSA in undiluted blood plasma could be measured in the low picomolar range, by recording the amplitude of the 2f signal (at twice the driving frequency). Vliembergen et al 124,125 have extended the optical detection method by analyzing the rotation-angle dependent scattering signals. Sharp peaks in the spectrum allowed them to measure nanometer-scale inter-particle distances within the clusters.…”
Section: Biomarker Detection and Concentration Determinationmentioning
confidence: 99%
“…For dimers, the scattered light from both individual particles is coupled and results in a spatial distribution of the scattered light that depends on their mutual distance and the dimer orientation with respect to the laser beam. The distance dependence is especially apparent for near-perpendicular scattering angles, 12 which is why a photodiode at 90° is used.…”
Section: Resultsmentioning
confidence: 99%
“…The values for the parameters are identical to those in a previous theoretical paper. 12 Specifically, the diameter of the particles is 1050 nm, the refractive index of the particles is n = 1.68 + 0.005 i , and the refractive index of the solution is 1.331. In the following, only scattering angles of 90° are considered, as these correspond to the measured PD signals at 90°.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations